TITAN MENURUT MISI CASSINI-HUYGENS: DISTRIBUSI ETANA DI ATMOSFERNYA - Ali Rafi', Sayyed
Ethane is one of the trace gases compounds with the highest abundance in Titan's atmosphere with a relatively constant distribution. Ethane also plays an important role in forming more complex hydrocarbons through various chemical reactions in the atmosphere. The hydrocarbon liquid on Titan's surface is also dominated by ethane because most of its abundance in the atmosphere is reduced through condensation. Therefore, ethane abundance is an interesting topic of study. This thesis focuses on determining the abundance of ethane in Titan's atmosphere, particularly in the stratosphere, by utilizing infrared spectrum data from the CIRS instrument onboard the Cassini spacecraft, which has been observing Titan for more than 12 years. There are 10 yby data used in the analysis and cover all parts of Titan's hemisphere and span over 7 years. Its abundance is obtained as a vertical prole so that it provides information about its distribution with respect to height. In addition, the distribution with respect to latitude will also be reviewed. The method used in this thesis is tting method using a radiative transfer and inversion model. The spectra modeled spans from 1275 to 1325 cm-1 (methane 4 band) and 803 to 840 cm-1 (ethane 12 band). Then, inversion method is used to derive atmospheric parameters that match the modeled spectrum. The rst modeling was carried out on the methane band to obtain the temperature. This temperature is then used to model the ethane band which is then used to obtain its abundance. The resulting vertical proles are all relatively constant with a mean abundance of not less than 1.110????5 and not more than 2.110????5 at 100-400 km. The pole enrichment pattern is also seen especially for the north winter pole in December, 2011, with an enrichment factor of around 1.1-1.4. This relatively constant abundance can be attributed to the long chemical lifetime of ethane in the atmosphere (about 730 years) so that it has ample time to diuse evenly. The process of the formation of polar vortices also have a role in enriching the molecular abundance at the poles.